Critical Observations on the Hymns of Callimachus - McLennan, Robert George (My University, 1970)
This thesis examines the structure and contents of the Hymns of Callimachus in comparison with earlier hymns and in the light of influence from other genres of Greek literature.
Keywords: Classics; Classics